Exploring HPV vaccination policy and payer strategies for opportunities to improve uptake in safety-net settings - Sloan, Kylie; Shin, Michelle; Palinkas, Lawrence A.; Hudson, Shawna V.; Crabtree, Benjamin F.; Cantor, Joel C.; Tsui, Jennifer (Frontiers in Public Health, 2023)
To explore priorities and perspectives on health policy and payer strategies for improving HPV vaccination rates in safety-net settings in the United States, we conducted qualitative interviews with policy and payer representatives in the greater Los Angeles region and state of New Jersey between December 2020-January 2022. Practice Change Model domains guided data collection, thematic analysis, and interpretation. Five themes emerged from interviews with 11 policy and 8 payer participants, including: 1) payer representatives not prioritizing HPV vaccination specifically in incentive-driven clinic metrics; 2) policy representatives noting region-specific HPV vaccine policy options; 3) inconsistent motivation across policy/payer groups to improve HPV vaccination; 4) targeting of HPV vaccination in quality improvement initiatives suggested across policy/payer groups; and 5) COVID-19 pandemic viewed as both barrier and opportunity for HPV vaccination improvement across policy/payer groups. Our findings indicate opportunities for incorporating policy and payer perspectives into HPV vaccine improvement processes. We identified a need to translate effective policy and payer strategies, such as pay-for-performance programs, to improve HPV vaccination within safety-net settings. COVID-19 vaccination strategies and community efforts create potential policy windows for expanding HPV vaccine awareness and access.